Bioaccessibility of phenolics from carob (Ceratonia siliqua L.) pod powder prepared by cryogenic and vibratory grinding. (30th May 2022) - Frühbauerová, Michaela; Červenka, Libor; Hájek, Tomáš; Pouzar, Miloslav; Palarčík, Jiří
Highlights: Cryogenically ground carob pulp had a higher phenolic content. More phenolics were released from the cryogenically ground sample after digestion. The phenolic compounds of vibratory ground samples were more bioaccessible. Abstract: Carob pod powder prepared by cryogenic (CG) and vibratory grinding for 4 min (VG-4) and 8 min (VG-8) was evaluated for its antioxidant properties, and phenolic content. The bioaccessibility of phenolics was determined after the oral, gastric, and intestinal digestion phases in vitro . CG carob powder had a higher total phenolic content (6.46 mg gallic acid/g) and antioxidant capacities in terms of DPPH (15.60 mg Trolox/g) and ABTS (28.58 mg Trolox/g) assays. Quercitrin (44.54–64.68 μg/g) and cinnamic acid (27.48–31.40 μg/g) were the most abundant phenolics in all carob powder samples determined by liquid chromatography. The bioaccessibility of only ferulic acid (108%) had increased after digestion of the CG carob powder. Vibratory grinding (VG-4 and VG-8) improved the bioaccessibility of cinnamic acid (86–87%), vanillic acid (87–95%), quercitrin (33–34%), and naringenin (19–22%). A better bioaccessibility of phenolic constituents was observed for vibratory ground carob powder.